Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5125/jkaoms.2012.38.6.354
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of age on skeletal stability after sagittal split ramus osteotomy for mandibular setback

Abstract: (J Korean Assoc Oral Maxillofac Surg 2012;38:354-9) Objectives: The purpose of this study was to investigate whether the age factor would be related with stability of mandibular setback surgery for patients with mandibular prognathism. Materials and Methods: We compared the relapse patterns of 47 patients divided into three age groups (termed younger, adult, and older). The younger group consisted of patients between 15 and 17 years old; the adult group was made up of patients between 21 and 23 years old, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…The duration of time required for recovery to the preoperative condylar position after orthognathic surgery has varied in previous studies, ranging from 6 months [15,17] to 3 years [34]. Lee et al [30] reported a trend of condyles returning to their preoperative position over time, which was consistent with the findings of this study (Table 2), demonstrating a common pattern of condylar displacement after surgery. The present study revealed significant positional changes between T0 and T2 only in the y-axis (p < 0.05: Table 2).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The duration of time required for recovery to the preoperative condylar position after orthognathic surgery has varied in previous studies, ranging from 6 months [15,17] to 3 years [34]. Lee et al [30] reported a trend of condyles returning to their preoperative position over time, which was consistent with the findings of this study (Table 2), demonstrating a common pattern of condylar displacement after surgery. The present study revealed significant positional changes between T0 and T2 only in the y-axis (p < 0.05: Table 2).…”
Section: Discussionsupporting
confidence: 87%
“…Lee et al [30] reported a significant increase in intercondylar distance due to lateral condylar movement in patients with asymmetry and mandibular prognathism. Similarly, our study found that patients with mandibular asymmetry (more than a 3 mm difference between the right and left setback amount) showed significant anterior movement between T0 and T1 (p = 0.003: Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation